Study on the Extraction of Mo(VI) in Nitric Acid by Ionic Liquid Cyphos IL 101 - Weidian WANG; Yuxuan WU; Rulei WU; Lei YANG; Yao LI; Haolin DONG; Xueqin XIANG; Jixin LIANG (Journal of Isotopes)
99Mo is an important medical radionuclide. Solvent extraction is one of the feasible methods for separating fission 99Mo from neutron-irradiated 235U targets in reactor. In this work，the extraction behavior of Mo(VI) in nitric acid system by ionic liquid Cyphos IL 101 was studied. The effects of diluent，initial pH value，extraction time，temperature，ionic liquid concentration and other factors on the extraction efficiency were investigated. The results showed that when toluene was selected as the diluent，high extraction efficiency of Mo(VI) was obtained. At pH 3，the extraction rate of Mo(VI) was over 98.87%. Meanwhile，it indicated that the extraction process was spontaneous，which could reach equilibrium within 5 min. When 1 mol/L Na2CO3 was selected as the stripping agent，96.56% of Mo(VI) could be re-extracted into the aqueous phase in one stripping. Mo(VI) could be separated over from some main fission impurities such as Sr，Cs，Te. This study is expected to pave the way for introduction of ionic liquid Cyphos IL 101 as an extraction agent for the separation process of fission 99Mo from irradiated uranium targets.